Patterns of choosins the means of translating words of category of state from Russian into French - Perzashkevich, Hanna A. (Journal of the Belarusian State University. Philology, 2026)
The article reviews practice, features and patterns of choosing the means of translating words of the category of state from Russian into French, based on the classical translation of L. N. Tolstoy’s novel «Anna Karenina». The study establishes a typology of translation means for Russian words of the category of state into French. The key translation strategies have been identified including the usage of impersonal constructions with the pronoun il, the usage of verbs, adverbs, nouns, or adjectives, as well as application of grammatical sentence transformation. The revealed patterns governing the choice of a specific strategy show their dependence on the semantic group of the predicative word and its contextual milieu.
Keywords: category of state; translation; impersonal construction; verb; adverb; noun; adjective; grammatical transformation; semantic group; L. N. Tolstoy